The Influence of Work Motivation, Job Satisfaction, Organizational Commitment, and Compensation on Employee Performance of J&T Express Banjarmasin - Gunarti, Anastasia Wahyu Tri; Agustina, Titien; Jaya, Fanlia Prima; Jatmika, Dodik (International Journal of Social Science, Education, Communication and Economics, 2024)
Employee performance is an important part of human resource management. Employee performance is influenced by work motivation, job satisfaction, organizational commitment, and compensation. Research on work motivation, job satisfaction, organizational commitment, and compensation among J&T Express Banjarmasin employees needs to be carried out to determine their influence on the performance produced by employees for the company. This research uses a quantitative approach with explanatory research. The research population consisted of 35 employees of J&T Express Banjarmasin. The sampling technique uses saturated or total samples with data collection methods via questionnaires. The data analysis technique uses multiple linear regression analysis. The results of the research show that the value of F table in df 4 and df 30 in table F is 0.69 with a significance of 0.000. The calculated F value reached 162.808. Work motivation, job satisfaction, organizational commitment, and compensation influence employee performance simultaneously and are accepted because F count > F table and significance is 0.000 <0.05. Work motivation has an effect on employee performance, shown with a significance of 0.001<0.05. Job satisfaction has an effect on employee performance, shown with a significance of 0.000 <0.05. Organizational commitment influences employee performance as shown with a significance of 0.000 <0.05. Compensation has an effect on performance because the significance is 0.001<0.05. Compensation has a dominant influence on performance. So work motivation, job satisfaction, organizational commitment, and compensation have a significant effect on the performance of J&T Express Banjarmasin employees partially and simultaneously. It is recommended that J&T Express Banjarmasin better manage work motivation, job satisfaction, organizational commitment, and compensation in order to improve employee performance even better.